Structure–Activity Relationships in Tripodal Transmembrane Anion Transporters: The Effect of Fluorination - Busschaert, Nathalie (American Chemical Society, 2011)
[Image: see text] A series of easy-to-make fluorinated tripodal anion transporters containing urea and thiourea groups have been prepared and their anion transport properties studied. Vesicle anion transport assays using ion-selective electrodes show that this class of compound is capable of transporting chloride through a lipid bilayer via a variety of mechanisms, including chloride/H(+) cotransport and chloride/nitrate, chloride/bicarbonate, and to a lesser extent an unusual chloride/sulfate antiport process. Calculations indicate that increasing the degree of fluorination of the tripodal transmembrane transporters increases the lipophilicity of the transporter and this is shown to be the major contributing factor in the superior transport activity of the fluorinated compounds, with a maximum transport rate achieved for clog P = 8. The most active transporter 5 contained a urea functionality appended with a 3,5-bis(trifluoromethyl)phenyl group and was able to mediate transmembrane chloride transport at receptor to lipid ratios as low as 1:250000. Proton NMR titration and single crystal X-ray diffraction revealed the ability of the tripodal receptors to bind different anions with varying affinities in a 1:1 or 2:1 stoichiometry in solution and in the solid state. We also provide evidence that the most potent anion transporters are able to induce apoptosis in human cancer cells by using a selection of in vitro viability and fluorescence assays.